MiR-425-5p intervenes in autoimmune myocarditis by regulating Treg cell differentiation through NRAS - Zhou, Shan; Zhang, Li; Duan, Xiuyun; Liu, Keyu; Yingnan, You; Ma, Mengjie; Han, Bo (Frontiers in Cell and Developmental Biology, 2025)
AimOur Previous research revealed significant differences in exosome-mediated intercellular miR-425a-5p between normal children and those with fulminant myocarditis. We sought to elucidate the molecular underpinnings and functional implications of miR-425a-5p in the context of myocarditis progression.MethodsBioinformatics techniques were employed to predict NRAS as the target gene of miR-425a-5p. We constructed a cellular myocarditis paradigm through LPS-mediated provocation of AC16 cardiomyocyte cultures. MiR-425a-5p was overexpressed, and the expressions of NRAS, cell apoptosis, and proinflammatory cytokine profiles, encompassing IL-1β, IL-6, and TNF-α, were comprehensively quantified. An experimental autoimmune myocarditis (EAM) mouse model was created using adeno-associated virus (AAV) for miR-425a-5p overexpression. Comprehensive histopathological analyses were conducted utilizing multiple staining techniques, including hematoxylin-eosin (HE), immunohistochemical, and Masson trichrome methodologies to characterize tissue responses.ResultsThe study demonstrated that miR-425a-5p alleviated the inflammatory response in both AC16 cells and EAM mice through NRAS mediation. Single-cell data analysis of cardiac immune cells revealed that miR-425a-5p promoted Treg cell differentiation and improved cardiac function.ConclusionMiR-425a-5p plays a crucial role in modulating inflammatory responses in myocarditis, potentially offering a novel therapeutic strategy for managing the disease.